Analisa pengaruh sakit tenggorokan terhadap perubahan spektrum suara - Sutono Sutono; Hendra Setiawan; Yusuf Aziz Amrullah (Health Sciences and Pharmacy Journal, 2017)
ABSTRACTBackground: Voice is a kind of sound produced by friction or vibration of objects. In humans vocal cords in throat are used to produce voice and the produced voice may have different frequency. Human voice in a kind of a sound created by several organ, such as lungs, laryngs, pharynx, nasal cavity, moulth cavity, moulth and tongue. The existence  of those organs will inluance the produced voice. Pharingitis is one of upper channel infection. Objective: To condact a analysis on the human voice because of sore throat, get a list of alphabeth that experience the biggest caused by sore throat, and to recognise the possibility of throat disorder seen by the analysis of frequency spectrum. Method: The research is conducted  by comparing the voice result post paryngistis and after being recoved. The research uses fourier transformation to compare the produced pattern by using MSE ( Mean Square Error). The researcher tested 7 respondents. Result: The result shows that there is influence towards the resulted voice. The Alphabeths that experiances the biggest disorder are A (MSE:0,094677), M (MSE:0,072883), L (MSE:0,095975), Z (MSE:0,07552), X (MSE:0,07602) dan K (MSE:0,119209), it can be concluded that each respondent has different alphabeth disorder.